Two-year real-world outcome data from a single tertiary centre shows reduced ustekinumab persistence in a non-bio-naïve Crohn's disease cohort with penetrating disease, -ostomies and sarcopenia - Saskia Inniss; Konstantinos C. Fragkos; Lisa Whitley; Rachel Wimpory; Eleanor Rebello; Ana Lisboa; Tanvi Khetan; Jasmine Hassan; Kate Simpson; Anisha Bhagwanani; Roser Vega; Ioanna Parisi; et al. (SAGE Publishing, 2023)
Background: Ustekinumab was approved in 2016 for the treatment of moderate-severe Crohn's disease (CD). Clinical trials and real-world studies have suggested ustekinumab to be a safe and effective treatment; however, studies to date infrequently use imaging techniques to predict response to biologics in CD. Objectives: We assessed the 2-year real-world effectiveness and safety of ustekinumab in a tertiary CD cohort with the use of novel imaging techniques. Design: Retrospective cohort study. Methods: Retrospective data were collected between 2016 and 2021. Study end points included ustekinumab persistence, biological and/or clinical response and remission at 12, 18 and 24 months. Statistical analysis included demographic and inferential analyses. Results: In all, 131 CD patients [57.3% female, median age of 26.0 (21.0-37.0)] were included. Patients were non-bio naïve, and the majority received ustekinumab as third- or fourth-line treatment. At 24 months, 61.0% (80/131) persisted with ustekinumab [52.7% (69/131) steroid free]. Clinical response was reported in 55.2% (37/67), clinical remission in 85.7% (57/67), biological response in 46.8% (22/47) and biological remission in 31.9% (15/47) of patients at 24 months. The low outcome numbers were attributable to missing data. Improvements in routine disease markers, including C-reactive protein and Harvey-Bradshaw Index, were also reflected in magnetic resonance imaging-derived disease scores. The presence of penetrating CD, an -ostomy and sarcopenia were all predictors of poorer ustekinumab outcomes ( p  < 0.05). Conclusion: Ustekinumab is effective in non-bio-naïve CD patients with non-stricturing, non-penetrating disease with an unremarkable safety profile but may be less effective in those with penetrating disease, -ostomies and sarcopenia.